Meredith Monk Book review - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 1999)
PALABRAS CLAVE: Meredith Monk, Atlas.
Meredith Monk. Edited by Deborah Jowitt, Johns Hopkins University Press, 1997.